Synaphobranchidae ... - Bañon, Rafael; Arronte, Juan Carlos; Rodriguez-Cabello, Cristina; Piñeiro, Carmen-Gloria; Punzon, Antonio; Serrano, Alberto (Zenodo, 2016)
Family Synaphobranchidae Synaphobranchus kaupii Johnson, 1862 —Kaup's arrowtooth eel 1,264 specimens were caught at depths between 711 and 1,809 m. Length data were available for 1,252 specimens ranging from 8 to 72 cm TL (21.8±11.4). Habitat and Distribution: demersal deep-sea fish between 120– 4,800 m depth, usually 400–2,200 m. Distribution in all major ocean basins: Atlantic, Indian, and Pacific oceans. In the eastern North Atlantic, it is recorded from west of the Faroe Islands slope to the coast of northwest Africa. Vulnerability: LC (IUCN), MHV (FishBase). ... : Published as part of Bañon, Rafael, Arronte, Juan Carlos, Rodriguez-Cabello, Cristina, Piñeiro, Carmen-Gloria, Punzon, Antonio & Serrano, Alberto, 2016, Commented checklist of marine fishes from the Galicia Bank seamount (NW Spain), pp. 293-333 in Zootaxa 4067 (3) on page 304, DOI: 10.11646/zootaxa.4067.3.2, http://zenodo.org/record/256670 ...